Chitosan-based biomaterial delivery strategies for hepatocellular carcinoma - Wang, Xianling; Yang, Yan; Zhao, Shuang; Wu, Di; Li, Le; Zhao, Zhifeng (Frontiers in Pharmacology, 2024)
Background Hepatocellular carcinoma accounts for 80% of primary liver cancers, is the most common primary liver malignancy. Hepatocellular carcinoma is the third leading cause of tumor-related deaths worldwide, with a 5-year survival rate of approximately 18%. Chemotherapy, although commonly used for hepatocellular carcinoma treatment, is limited by systemic toxicity and drug resistance. Improving targeted delivery of chemotherapy drugs to tumor cells without causing systemic side effects is a current research focus. Chitosan, a biopolymer derived from chitin, possesses good biocompatibility and biodegradability, making it suitable for drug delivery. Enhanced chitosan formulations retain the anti-tumor properties while improving stability. Chitosan-based biomaterials promote hepatocellular carcinoma apoptosis, exhibit antioxidant and anti-inflammatory effects, inhibit tumor angiogenesis, and improve extracellular matrix remodeling for enhanced anti-tumor therapy. Methods We summarized published experimental papers by querying them. Results and Conclusions This review discusses the physicochemical properties of chitosan, its application in hepatocellular carcinoma treatment, and the challenges faced by chitosan-based biomaterials.